The effect of the operating conditions on the apparent viscosity of crude palm oil during separation - Al-Zuhair, Sulaiman; Abakrb, Yousif A.; Ahmed, Mirghani Ishak (IIUM Press, 2011)
This paper discusses the apparent viscosity of crude palm oil, using rotary viscometer, under different boundary conditions. It was experimentally shown that the apparent viscosity of palm oil drops with increasing shear rate and temperature. However, the effect of temperature on the viscosity tends to fade at temperatures beyond 80"C. A correlation between the apparent viscosity of crude palm oil and the operating conditions was developed. The derived correlation represents well the experimental data. This correlation can be used in design of crude palm oil settlers and in determining the optimum operating conditions.